Pengembangan Motorik Halus Anak Usia Dini melalui Permainan Pasir Kinetik di Kelompok B Pratama Widya Pasraman Gurukula - I Gde Suryawan; Ni Wayan Kasriani (Texture:Art and Culture Journal, 2023)
Early childhood is experiencing a process of rapid growth and development. In this case,  stimulation is needed to develop aspects of child development. One of the child's development that needs to be developed is fine motor skills. Early childhood education is a means to develop children's fine motor skills through a variety of fun games. Kinetic sand play activities are activities that can develop children's fine motor skills. Kinetic sand is a learning medium in the form of sand that is flexible, easy to shape and liked by children. The purpose of this study was to determine motor development activities through playing kinetic sand in Group B Pratama Widya Pasraman Gurukula Bangli. This study uses qualitative methods to convey research results descriptively. Data collection techniques in this study are observation, interviews and documentation. The results of this study were that early childhood fine motor development activities in Group B Pratama Widya Pasraman Gurukula Bangli through kinetic sand games had a significant impact on children's fine motor development. By squeezing, holding, pressing and shaping kinetic sand, it can stimulate the muscles of the child's arms so that fine motor skills can develop properly.